Brand Image and Brand Awareness to The Success of The Beverage Business in The Market International (Case Study of Mixue Condet Raya) - Saad, Bani; Nugraha, Rizki Nurul (West Science Journal Economic and Entrepreneurship, 2024)
This research discusses brand image and brand awareness which have an important role in influencing the success of beverage businesses in the international market. The case study on Mixue Condet Raya provides a specific focus on the relevant context to gain deeper insights. This research has urgency in providing a better understanding of how brand image and brand awareness can shape the success of beverage businesses in the international market. The results of the research can provide strategic guidance to businesses in managing their brands effectively. This research uses a descriptive qualitative approach with survey methods, interviews, and is assisted by SWOC Analysis to identify the strengths, weaknesses, opportunities and challenges in Mixue's success on an international scale. This research can help Mixue Condet Raya to be able to maintain its business on an international scale, especially Indonesia.